Effects of Lipid Shape and Interactions on the Conformation, Dynamics, and Curvature of Ultrasound-Responsive Liposomes - Hwankyu Lee; Hyungwon Moon; Hyun-Ryoung Kim (MDPI AG, 2022)
We perform coarse-grained molecular dynamics simulations of bilayers composed of various lipids and cholesterol at their different ratios. Simulations show that cholesterol-lipid interactions restrict the lateral dynamics of bilayers but also promote bilayer curvature, indicating that these opposite effects simultaneously occur and thus cannot significantly influence bilayer stability. In contrast, lyso-lipids effectively pack the vacancy in the bilayer composed of cone-shaped lipids and thus reduce bilayer dynamics and curvature, showing that bilayers are more significantly stabilized by lyso-lipids than by cholesterol, in agreement with experiments. In particular, the bilayer composed of cone-shaped lipids shows higher dynamics and curvature than does the bilayer composed of cylindrical-shaped lipids. To mimic ultrasound, a high external pressure was applied in the direction of bilayer normal, showing the formation of small pores that are surrounded by hydrophilic lipid headgroups, which can allow the release of drug molecules encapsulated into the liposome. These findings help to explain experimental observations regarding that liposomes are more significantly stabilized by lyso-lipids than by cholesterol, and that the liposome with cone-shaped lipids more effectively releases drug molecules upon applying ultrasound than does the liposome with cylindrical-shaped lipids.